2021
DOI: 10.3390/su13137111
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Perceptions of Emotions and Self-Regulatory Learning in Emergency Remote Learning

Abstract: This study explored emotions and self-regulatory learning in postgraduate students, forced to transition to emergency remote teaching, at a Hong Kong university after the start of the academic semester. Self-regulation is a critical factor for successful online learning, and emotions are important antecedents of self-regulated learning. The study adopted a two-phase research design, with an initial online questionnaire (n = 52) followed by semi-structured interviews (n = 16) to gain a rich and holistic underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Instructors and institutions have employed blended approaches [10,60] and fully online courses designed for synchronous delivery [61]. However, the migration to emergency remote teaching brought new and unexpected challenges [16,62], and teachers had to adjust their pedagogical practices [2,[44][45][46]. This study allowed us to explore how EAP teachers coped pedagogically with the transition.…”
Section: Discussionmentioning
confidence: 99%
“…Instructors and institutions have employed blended approaches [10,60] and fully online courses designed for synchronous delivery [61]. However, the migration to emergency remote teaching brought new and unexpected challenges [16,62], and teachers had to adjust their pedagogical practices [2,[44][45][46]. This study allowed us to explore how EAP teachers coped pedagogically with the transition.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study can be compared with 10 of these relevant papers [68][69][70][71][72][73][74][75][76][77]. While other researchers have analyzed the effects of ERT on high school teachers [68], state universities [69], and the challenges faced by educational institutions [70], for the proposed model, the developed EvalMathI system was tested to be able to answer questions Q1-Q4, questions that support the development of the model for the evaluation system (LAEM), and also validate the software instrument called EvalMathI.…”
Section: Discussionmentioning
confidence: 99%
“…The authors answered Q1—How useful is EvalMathI in evaluating courses in an ERT situation?—by introducing and integrating the dashboard in a responsive panel to facilitate and streamline the evaluation process. In addition, other researchers have previously analyzed students’ performance in an ERT situation [ 71 ], the challenges faced by math teachers in an ERT situation [ 72 ], the level of emotions in the learning process [ 75 ], the factors influencing home learning [ 78 ], and students’ emotions and the perception of teachers in ERT [ 76 , 77 ]. In this context, the present study analyzed the methodology of evaluation in ERT conditions and proposed a tool called EvalMathI, which was tested in a case study of six courses conducted in ERT at our university.…”
Section: Discussionmentioning
confidence: 99%
“…Combining an online questionnaire (n = 52) and interviews (n = 16), Kohnke, Zou, and Zhang [35] looked at learner emotions, self-regulated strategies, and perceived difficulties of Chinese FL students in an ERT setting. The authors found that students enjoyed attending the ERT classes and felt that they were able to develop their L2 skills online.…”
Section: Learner Emotion Research In Emergency Remote Teaching Contextsmentioning
confidence: 99%